Frequency of the Dengue Fever in Patients with Acute Febrile Illness at Diagnostic & Research Laboratory, Hyderabad - Chang, Abid Hussain; Memon, Faheem Ahmed; Kirshan, Jai; Detho, Ameer Bux; Mangi, Muhammad Muqeem; Memon, Khalid Yousif (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To determine the frequency of dengue fever in patients with acute febrile illness and to evaluate the clinical profile of dengue positive cases. METHODOLOGY: This cross sectional, descriptive study was conducted at Diagnostic & Research Laboratory, LUMHS Hyderabad, Samples of the patients having history of acute febrile illness, within the period of June 2018 to August 2018, were confirmed for the presence of dengue IgM antibody and NS1 antigen. Dengue IgM antibody was detected by using the technique enzyme linked immunosorbent assay (ELISA) while dengue NS1 antigen was detected by immune-chromatographic technique (ICT) rapid device. Clinical and hematological findings were also recorded. RESULTS: An aggregate of 11250 cases presented with classical characteristics of Dengue fever were collected out of which majority of the cases were in there third decade of life expectancy with median age of 30 years. Seventy four percent (74%) i-e 8,325 patients were tested were found to be positive for dengue virus and remaining 2,925 (26%) appeared to be negative for dengue; from which 900 (8%) were positive for malarial parasite, 675 (6%) were diagnosed with typhoid fever and strikingly 1350 (12%) patients remained undiagnosed. CONCLUSION: Fever along-with body ache followed by vomiting and abdominal pain were found to be the common characteristic symptoms of Dengue fever.